INCREASED RISKS OF ATHEROSCLEROTIC HEART DISEASE, MALIGNANCY AND SLEEP APNEA WITH PRIMARY ALDOSTERONISM - Shakir, Mohamed; Bonsu, Osei; Vasnthakumar, Vijaykiran; Hoang, Thanh (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Primary aldosteronism (PA) is associated with increased risks of atherosclerosis, malignancy, and sleep apnea. We report a case of untreated PA complicated by coronary artery disease (CAD), renal cell carcinoma (RCC) and sleep apnea during the course of the illness. CASE Laboratory and radiological studies were performed at our hospital. A 51-year-old male had a 12-year history hypertension and hypokalemia. His laboratory tests then showed plasma renin activity (PRA) 0.06 ng/mL/hr, aldosterone 6 ng/ dL, normal plasma metanephrines and dexamethasone suppression test. Despite using several anti-hypertensive medications, his hypertension and hypokalemia remained poorly controlled. He was also diagnosed with sleep apnea and was placed on CPAP. At the age of 47 years, a diagnosis of Liddle syndrome was considered, and he was placed on amiloride. The following year, he was diagnosed with coronary artery disease. Repeat laboratory showed PRA <0.167 ng/ml/hr and plasma aldosterone 111.4 ng/dL. An abdominal CT revealed a left adrenal adenoma and a 1.8 cm left renal lesion suggestive of RCC. Adrenal venous sampling localized the left adrenal adenoma as the cause of PA. The patient underwent left adrenalectomy and left partial nephrectomy. Histopathology confirmed the diagnosis of adrenal adenoma and RCC. One week later, plasma aldosterone was 1.9 ng/dL and his hypertension improved with fewer medications without requiring potassium supplementation. CONCLUSION Our case illustrates that delayed diagnosis of PA may be associated with an increased risk of CAD, malignancy and sleep apnea. Early diagnosis and surgical intervention are recommended for aldosterone-producing adenoma.